2018
DOI: 10.3989/mc.2018.01717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hybrid fibers, calcium carbonate whisker and coarse sand on mechanical properties of cement-based composites

Abstract: Nowadays researchers are developing a new hybrid fiber reinforced cement-based composites (HyFRCC). The new HyFRCC can restrain micro-cracking, improves compressive and flexural performance of beams by addition of calcium carbonate (CaCO 3 ) whisker, polyvinyl alcohol (PVA) fiber and steel fiber. In this work, a mix optimization procedure is shown for multi-scale HyFRCC, with steel, PVA fiber and CaCO 3 whisker. The new HyFRCC is explored with addition of coarse sand to further improve its mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…The behavior of FRCC depends on many factors, such as composite mixture characteristics, fiber characteristics, and base matrix characteristics 30,34 . From the existing literature, a significant work had been done on static properties of multiscale hybrid fiber reinforced cementitious composite (MSHFRCC) using steel fiber, PVA fiber, and CaCO 3 whisker 26,27,35–43 . However, material properties of steel fiber, PVA fiber, and CaCO 3 whisker FRCC under dynamic load are not studied yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of FRCC depends on many factors, such as composite mixture characteristics, fiber characteristics, and base matrix characteristics 30,34 . From the existing literature, a significant work had been done on static properties of multiscale hybrid fiber reinforced cementitious composite (MSHFRCC) using steel fiber, PVA fiber, and CaCO 3 whisker 26,27,35–43 . However, material properties of steel fiber, PVA fiber, and CaCO 3 whisker FRCC under dynamic load are not studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…The improved performance of PVA fiber is also observed in Engineered Cementitious Composite (ECC) 24,25 . Calcium carbonate (CaCO 3 ) whisker is new types of micron fiber with low production cost which resists cracking at the micro level 26–29 . The FRCC material must be designed for resisting the dynamic loading by enhancing its energy absorption capability 30 .…”
Section: Introductionmentioning
confidence: 99%
“…It is different from limestone powder with a bulk shape [ 35 ] or granular shape (see in Figure 6 ), but is needle-like [ 56 ] (see in Figure 7 ). Because of its shape, CW not only fills the voids to make the matrix dense [ 14 ] but also plays a role in resisting the development of micro-cracks, especially with incorporated steel fiber [ 16 , 20 , 59 ], PVA fiber [ 15 ] and carbon fiber [ 60 ]. Moreover, a positive synergic effect can be demonstrated when incorporated of a hybrid fiber system [ 61 , 62 ].…”
Section: Micro-calcium Carbonatementioning
confidence: 99%
“…Incorporation of SCMs and mineral admixtures such as fly ash, slag, silica fume and limestone is not only an effective way to reduce the carbon dioxide emissions and sources consumption, but also an economic and environmentally friendly way to produce cement or concrete, because most SCMs and mineral admixtures are industrial waste products [ 4 ]. Among these SCMs and mineral admixtures, limestone is widely used as a kind of filler material [ 5 , 6 , 7 , 8 , 9 ], aggregate [ 10 , 11 , 12 , 13 ], micro-fiber [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ] and early strength agent [ 21 ] because of its various scales (macro-, micro- and nano-scale) [ 2 , 22 ], morphologies (bulk, granular and fibrous shape), crystal systems (calcite, aragonite, vaterite and amorphous calcium carbonate) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…25SP0.75, SS1.5LP0.5, SS1.25LP0.75, LS1.5SP0.5, LS1.5LP0.5 and LS1.25LP0.75, respectively. This indicated that addition of CW into PVAsteel fiber specimens could increase compressive strength because micro-sized CW filled pores of matrix and improve the compactibility of cubes(12,17). However, compared with LS1.25SP0.75, the compressive strength of LS1.25SP0.55CW2.0 was decreased by 16.4%which is probably related…”
mentioning
confidence: 90%